Associations Between Personality Traits and Adherence to Antidepressants Assessed Through Self-Report, Electronic Monitoring, and Pharmacy Dispensing Data: A Pilot Study. Issue 5 (October 2016) - Wouters, Hans; Amin, Darya F.H.; Taxis, Katja; Heerdink, Eibert R.; Egberts, Antoine C.G.; Gardarsdottir, Helga
Abstract : Abstract: Treatment with antidepressants is often compromised by substantial nonadherence. To understand nonadherence, specific medication-related behaviors and beliefs have been studied, but less is known about broader and temporally stable personality "traits." Furthermore, adherence has often been assessed by a single method. Hence, we investigated associations between the Big Five personality traits and adherence assessed by self-report, electronic drug use monitoring, and dispensing data. Using the Big Five Inventory, we assessed the personality traits "openness, " "conscientiousness, " "extraversion, " "agreeableness, " and "neuroticism" of patients treated with antidepressants who were invited through community pharmacies. Self-reported adherence was assessed with the Medication Adherence Rating Scale (score >24), electronic monitoring with medication event monitoring system (MEMS) devices (therapy days missed ⩽ 10% and < 4 consecutive days missed), and dispensing data (medication possession ratio ≥ 80%). One hundred four women and 33 men participated (mean age, 51; standard deviation, 14). Paroxetine was most frequently prescribed (N = 53, 38%). Logistic regression analysis revealed that of the personality traits, the third and fourth quartiles of "conscientiousness" were associated with better self-reported adherence (odds ratio, 3.63; 95% confidence interval, 1.34–9.86 and odds ratio, 2.97; 95% confidence interval, 1.09–8.08; P ⩽ 0.05). No relationships were found between personality traits and adherence assessed through electronic drug use monitoring or dispensing data. We therefore conclude that adherence to antidepressant therapy seems to be largely unrelated to personality traits.